Bridging Reflection and Critical Thinking: A Problem-Based Learning Approach to Digital Social Issues in Sociology Education - Rintia Rintia; Siti Nurbayani; Wilodati Wilodati; Mohamad Fauzi Sukimi (Jurnal Pendidikan Progresif, 2026)
This study aims to analyze how integrating the Problem-Based Learning (PBL) model with stages of sociological thinking enhances students' ability to respond to real-world social issues in the digital era. The study used a mixed-method approach with a sequential explanatory design. The quantitative stage involved 89 grade XII social studies students at one of the State High Schools in Bandung who participated in PBL-based Sociology learning. Data were collected through an essay test that measured four indicators of sociological thinking: common issue, reflective thinking, creative thinking, and critical thinking. The analysis was carried out descriptively and correlatively. The qualitative stage is conducted through interviews to deepen and explain the quantitative findings. The results of the study showed variation in achievement between indicators and between classes. Reflective and critical thinking indicators show a higher tendency to achieve, while common issues exhibit greater variation in distribution. Correlation analysis showed positive relationships, with moderate-to-strong correlations among all indicators, particularly between reflective thinking and critical thinking. Qualitative data indicate that the reflective and creative stages serve as a cognitive bridge to critical thinking when responding to digital social issues. Sociological thinking develops into a structured, integrated process. The integration of PBL with the sociological thinking stage supports the formation of reflective, creative, and critical student responses to actual social issues in the digital era. These findings confirm the importance of systematic learning design in building students' social awareness and digital responsibility. Keywords: building students' abilities, actual social issues, digital era, sociological thinking